2016
DOI: 10.1111/bcpt.12545
|View full text |Cite
|
Sign up to set email alerts
|

Sydnone 1: A Mesoionic Compound with Antitumoral and Haematological Effects In Vivo

Abstract: This study evaluated the antitumour activity of the mesoionic compound sydnone 1 (Syd-1) against Walker-256 carcinosarcoma. Tumour cells were subcutaneously inoculated in the hind limb in male Wistar rats. The animals were orally treated for 12 days with Syd-1 (75 mg/kg) or vehicle. At the end of treatment, considerable decreases in tumour volume and tumour weight were observed in treated animals. Samples of these tumours presented increases in apoptotic bodies and pro-apoptotic protein expression (Bax and p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It is one of the most widely used transplantable tumors in experimental research (Justice, 1985; Brigatte et al, 2007; Fan et al, 2016; Gambeta et al, 2016; Gao et al, 2016; Sroka et al, 2016; Wu M. et al, 2016). Indeed, these cells are one of the most preferred cell lines because of the ease with which they can be standardized, maintained and propagated in vitro , as well as their extensive use in vivo since 1937 (Michaelson and Orcutt, 1957; Brigatte et al, 2016; Galuppo et al, 2016; Pigatto et al, 2016; Trashkov et al, 2016; Yalovenko et al, 2016). …”
Section: Suitability Of Walker 256 Cellsmentioning
confidence: 99%
“…It is one of the most widely used transplantable tumors in experimental research (Justice, 1985; Brigatte et al, 2007; Fan et al, 2016; Gambeta et al, 2016; Gao et al, 2016; Sroka et al, 2016; Wu M. et al, 2016). Indeed, these cells are one of the most preferred cell lines because of the ease with which they can be standardized, maintained and propagated in vitro , as well as their extensive use in vivo since 1937 (Michaelson and Orcutt, 1957; Brigatte et al, 2016; Galuppo et al, 2016; Pigatto et al, 2016; Trashkov et al, 2016; Yalovenko et al, 2016). …”
Section: Suitability Of Walker 256 Cellsmentioning
confidence: 99%
“…Therefore, they attributed sydnone activity to the activation of apoptosis pathways by decreasing the expression of anti-apoptotic enzyme Bcl-2 and increasing both apoptotic bodies and proapoptotic proteins (Bax and p53). However, splenomegaly was observed in the treated animals, and it was linked to sydnoneinduced extravascular hemolysis [66].…”
Section: Cytotoxic and Anticancer Activitymentioning
confidence: 96%
“…[40,41] As shown in Figure 9, CA4P treated tumoursw ere significantly more necrotic than the untreated tumours, However,t reatment with 23 did not have an effect on tumour necrosis. Such al ack of response to 23 indicated that the compound mayn ot have reached the tumourb lood vessels and was either metabolised before it could act or it was rapidly excreted.O nly limited examples of mesoionic compounds have been tested in vivo [42,43] and their unusual structure makesi td ifficult to predict their pharmacokinetic profile and stability in the body.N onetheless,t his class of heterocycle has been ap opulart arget in medicinal chemistry over several years,a nd the establishmento fav iable administration route is therefore an important issue to address in the field. Further advancesi nt his area are the subjecto fa ctive investigation.…”
Section: In Vivo Studiesmentioning
confidence: 99%